Teaching English as a Foreign Language in Indonesia: A Guideline for Vocabulary Instruction - Sudarman Sudarman; Sunarti Sunarti; Elsa Widya Hapsari (Acitya: Journal of Teaching and Education, 2022)
This article aims to provide some guidelines for teachers on how to conduct vocabulary instruction in their class because one of the main issues faced by Indonesian students recently is the lack of vocabulary knowledge that affects their English proficiency. Some studies showed that Indonesian students did not even know most of essential words in English, known as high frequency words. As a result, they may struggle to use the language in communication. Therefore, English teachers need to focus on helping students develop their vocabulary knowledge by teaching new words based on students’ need and introducing some vocabulary learning strategies that they can use to learn unknown words on their own at home. In order to provide a guideline for vocabulary instruction, this paper reviewed studies related to vocabulary knowledge, English proficiency, and vocabulary instruction in Indonesian context. The result of this study provides a guideline that could help teachers improve their students’ vocabulary knowledge in teaching unknown words and vocabulary learning strategies. This paper also suggests English teachers to conduct their own research to determine which strategies work best for their students, so students can apply that strategies to learn unknown words autonomously.